Consistency of Mobile Payment Usage, Performance, and Financial Inclusion - Christiana Fara Dharmastuti; Stevanus Pangestu; Teresia Angelia Kusumahadi (Business and Entrepreneurial Review, 2022)
The development of financial technology impacts different human lives, including business processes. The public increasingly favors mobile payment as a fintech application because of its practicality, ease, and speed. In addition, its application could improve business performance and financial inclusion for business people. This study aims to analyze the consistency of mobile payment usage that will impact tenant performance and financial inclusion, influenced by perceived risk, perceived benefit (return), and brand image of mobile payment. The sample used in this study consisted of 338 respondents who are business people in the Jabodetabek area who use mobile payments.The results showed that perceived benefit and image influence business people to consistently use mobile payments in their business, which will impact business performance and increase their financial inclusion.The managerial implication for fintech companies is to maintain product quality and the benefits of mobile payments. People often ignore the risks of using mobile payments, so fintech companies mustmaintain their performances in terms of information, fraud, and speed of response to reduce consumer risks.